MENGENAL KAMPANYE KOMUNIKASI - Sumaina Duku (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2011)
This article aimed to describe communication campaign in social field include planning, process, and evalution. Communication campaign is a coodinated use of different methods of communication aimed at focusing attention on particular problem and its solution over a period of time. Public communication campaign as purposive attempt to inform, persuade, or motivate behavior changes in a relatively well-defined and large audience, generally for noncommercial benefits to the individual and/or society, typically within a given time period, by means of organized communication activities involving mass media and often complemented by interpersonal support.